The Impact of Earnings Management, Working Capital, Financial Distress, and Inflation On Financial Performance of Consumer Non-Cyclicals Sector Companies (Focus: Food And Beverage) Listed In IDX From 2020 to 2022 - Sujarminto, Aditya; Pratiwi, Safira Intan; Noviyanti, Eka (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This research investigates the impact of earnings management, working capital, financial distress, and inflation on the financial performance of Consumer Noncyclical sector companies, with a specific focus on the food and beverage industry listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022. Utilizing a quantitative approach and multiple linear regression analysis, the study analyses panel data from 38 selected companies to explore the relationships between these variables and Return on Assets (ROA). The findings reveal that earnings management significantly and positively influences ROA while working capital exhibits no significant impact. Financial distress emerges as a crucial factor positively affecting financial performance, while inflation shows no significant influence on ROA. The overall model explains 43.1% of the variation in ROA, providing nuanced insights into financial management practices. This study contributes valuable insights to financial management literature, guiding practitioners and policymakers in optimizing these determinants for enhanced financial outcomes in the food and beverage sector.